Identification of novel blood-based extracellular vesicles biomarker candidates with potential specificity for traumatic brain injury in polytrauma patients - Schindler, Cora R.; Hörauf, Jason A.; Weber, Birte; Schaible, Inna; Marzi, Ingo; Henrich, Dirk; Leppik, Liudmila (Frontiers in Immunology, 2024)
Objective: The goal of this study was to identify changes in extracellular vesicles (EV) surface proteins specific to traumatic brain injury (TBI), which could be used as diagnostic and prognostic tool in polytrauma patients.Summary Background Data: Known serum TBI-specific biomarkers (S100B, NSE and GFAP), which can predict the severity and outcome of isolated TBI, lose their predictive value in the presence of additional extracranial injuries . Extracellular vesicles (EVs) are released from cells in response to various stimuli and carry specific cargo/surface molecules that could be used for tracking injury-responding cells.Methods: EVs were isolated using size exclusion chromatography (SEC) from plasma of two groups of patients (with isolated TBI, ISS≥16, AIShead≥4, n=10; and polytraumatized patients without TBI ISS≥16, AIShead=0, n=10) collected in the emergency room and 48 h after trauma. EVs' surface epitopes expression was investigated using a neurospecific multiplex flow cytometry assay and compared with healthy controls (n=10). Three enrichments of EV epitopes found to be specific to TBI-was validated by western blot.Results: The expression of ten EVs epitopes differed significantly among the patient and control groups, and five of these epitopes (CD13, CD196, MOG, CD133 und MBP) were TBI-specific. The increased expression of CD196, CD13 and MOG -positive EVs was validated by western blot. Conclusions: Our data showed that TBI is characterized by a significant increase of CD13, CD196, MOG, CD133 und MBP -positive EVs in patients' plasma. A high level of MOG-positive EVs negatively correlated with the Glasgow Coma Scale score at admission and could be an indicator of poor neurological status.